Preparing children for climate-related disasters - Seddighi, Hamed; Yousefzadeh, Sepideh; López López, Mónica; Sajjadi, Homeira (BMJ Paediatrics Open, 2020)
Climate-related disasters affect different dimensions of children’s health and well-being both directly and indirectly. Reducing children’s vulnerability and exposure to climate-related disasters is crucial to protect them against risks. Children as climate-change agents and future leaders at local, national and international level can obviously contribute to reduce vulnerabilities in families and communities and transfer knowledge to them. Moreover, children can advocate for climate change mitigation. In the long term, participation of children in the climate change mitigation programmes may lead to fewer disasters and, consequently, less risk to their health., As government policies have failed to fully address and respond to the drivers of climate-related disasters, disasters preparedness and education for children should be considered an essential activity to protect children from disaster’s risks., Main factors in shaping children’s behaviour and response to disaster are increasing the risk perception and knowledge of the children. When a child perceived likelihood, susceptibility and severity of a disaster (such as earthquake), then they would be able and willing to learn how to prepare for that., So far, disaster education programmes for children have mostly relied on offline school-based training. Different innovative approaches can be applied to continue education within online and digital formats including virtual reality, digital games and online platforms. However, an advocacy support by influential entities such as companies engaged in entertainment industry is required to raise the awareness of public and particularly the children about disaster preparedness.

Youth Transitions: Creating Pathways to Success - Hughes, Deirdre; Smith, Graeme (Education Development Trust, 2020)
Around the world, young people face considerable challenges. Even before the disruption of the Covid-19 crisis, policymakers were seeking to respond to rapid technological advances, climate change and -- in some countries -- an ageing population and workforce. While children and young people worldwide generally have high aspirations and ambitions for their futures, evidence shows that they often face problematic and protracted transitions into work. In this context, new pathways from school to employment are needed. In this paper, we review extensive evidence to provide guidance on how children and young people can be best prepared to succeed in their school-to-work transitions, both now and in the future.
Keywords: 21st Century Skills; COVID-19; Career Development; Career Education; Economic Climate; Education Work Relationship; Educational Policy; Employers; Foreign Countries; Job Skills; Labor Market; Pandemics; Public Policy; Social Change; Technology Uses in Education; Vocational Education; Youth Employment

Climate Change Impact on Education - Weng, Boey Chun; Morooka, Rina; Mujtaba, Rustam Shariq; Shitong, Yang (Aide et Action, 2020)
Research report done for Aide et Action On selected ASEAN Countries (Cambodia, Vietnam, Laos PDR)
Keywords: Added through targeted search; ⛔ No DOI found; ⛔ No INSPIRE recid found

Build back better: Education must change after COVID-19 to meet the climate crisis - Giannini, Stefania (UNESCO, 2020)

Low-cost emerging technologies as a tool to support informal environmental education in children from vulnerable public schools of southern Chile - Alò, Dominique; Castillo, Andrea; Marín Vial, Paula; Samaniego, Horacio (International Journal of Science Education, 2020)
Reform to the Chilean educational system seeks to improve public education, adapting the school curriculum to new technologies and the information revolution. Our study focused on highlighting potential issues with environmental and technological education, offering opportunities to complement the current Chilean curriculum with an interdisciplinary approach. During a five-week period interspersed through the school semester, 115 underprivileged children in seventh grade from five public schools of southern Chile participated in workshops based on Arduino technology to address current environmental problems caused by global change and anthropization. Surveys were conducted to participating students and included both open and closed-ended questions, which measured attitudes and perceptions towards science and the use of technology in classrooms and daily lives. Surveys were analysed quantitatively with basic statistics and qualitatively by building semantic networks of the relationships between different concepts expressed by the students. Results did not show significant changes in attitudes towards science or technology before and after the workshops but students reported mixed feelings about science. Indifference and fear emerged, coupled with the need for more interactive experiences. Curiosity and enthusiasm also surfaced when students were using new technologies. Since the school curriculum is generally focused exclusively towards the completion of specific curricular aims, highly vulnerable schools in Chile have few opportunities to access interactive, hands-on activities. Low-cost, emergent technologies, such Arduinos, have a high potential for improving student's attitude towards science and technology and their use should be considered when tailoring school curriculum in Chile and elsewhere.
Keywords: 21CC abilities; Arduino; climate change; hands-on; information and communication technology; project-based learning

Reimagining our Future: Building Back Better from COVID-19 - UNICEF (2020)
This report presents the need to link COVID-19 recovery and response to climate and environmental action and details UNICEF's proposed solutions to reduce the impact of COVID-19 that can at the same time create a foundation for a greener, more sustainable future for children.
Keywords: ⛔ No INSPIRE recid found

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance Note 6 Digital technologies and education in Small Island Developing States (SIDS) From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH